Development of Teaching Materials to Support Learning of the Merdeka Curriculum on Chemical Equilibrium - Rizal, Putri Nadia; Mawardi, Mawardi; Suryani, Okta (research, training and philanthropy institution Natural Aceh, 2024)
Teaching materials are an essential part of independent curriculum learning. This study aims to determine valid and practical teaching materials on chemical equilibrium material that can support learning the independent curriculum phase F SMA / MA. The research used the Education Design Research type of research with the Plomp development model. The research includes development stages up to prototyping and testing in small groups. The instruments used were a validity questionnaire and a practicality questionnaire. Validity was assessed using the Aikens ' V formula modified by Purwanto to assess practicality Purwanto. The results showed that the validity test obtained 0.86 with a valid category. The results of the practicality test for teacher responses were obtained at 95% with an efficient category, and for student responses, obtained at 95% with an efficient category. These results state that the teaching materials created and developed are valid and practical. Then, the results showed that the multilevel representation approach emphasizes mastery at the macroscopic, submicroscopic, and symbolic levels. Mental models can be used to describe these three levels. A good mental model can help students relate scientific concepts to their thinking.